TraceRoot: A Blockchain-Based Traceability Framework for Enhancing Transparency and Trust in Rice and Essential Goods Supply Chain - Md. Safaet Hossain; Mohammad Shakibul Hasan Sakib; Md. Rayhan Ahmed Shis; Sakib Ahmed; Md. Fudail (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2026)
Modern food supply chains, particularly those involving essential commodities like rice, often suffer from major challenges such as product fraud, inefficient record-keeping, and a lack of consumer trust. Traditional centralized systems are prone to data tampering, limited transparency, and poor traceability, making it difficult to verify the authenticity and origin of goods. To address these issues, our research introduces TraceRoot, a blockchain-based traceability framework designed to enhance transparency, accountability, and trust in agricultural supply chains.TraceRoot leverages the immutability and decentralization of blockchain technology to maintain a secure, distributed ledger that records every transaction and movement of goods across the supply chain. Each stakeholder including farmers, distributors, retailers, and consumers has role-based access to authenticated data through a user-friendly interface. The framework integrates smart contracts to automate transactions and digital signatures to verify the integrity of the data being uploaded, minimizing the risk of human error or manipulation